2013
DOI: 10.1155/2013/845125
|View full text |Cite
|
Sign up to set email alerts
|

Dyskeratosis Congenita: A Report of Two Cases

Abstract: Oral manifestations play an important role in the diagnosis of many systemic conditions. Dyskeratosis congenita (DC) is a rare genodermatosis which exhibits oral leukoplakia, nail dystrophy, and reticular skin pigmentations as its primary features. DC has increased risk of developing constitutional anemias and malignancies and early diagnosis enables the patient to be monitored and proper interventional therapy to be instituted. Hence, dentists need to be aware of the various manifestations of this fatal syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 7 publications
0
22
0
4
Order By: Relevance
“…However, one of our two cases showed atypical radiologic and histopathologic features for UIP and also revealed quite prominent lymphatic proliferation, the significance of which is not entirely clear. A case study mentioned pulmonary vascular abnormalities in DC without any further elaboration of the details (13,14). A previous study on familial idiopathic interstitial pneumonia (F-IIP) cases enrolled in a national research program reported that, despite fibrosis in all cases, the diagnostic features of UIP were seen in less than 50% (15).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, one of our two cases showed atypical radiologic and histopathologic features for UIP and also revealed quite prominent lymphatic proliferation, the significance of which is not entirely clear. A case study mentioned pulmonary vascular abnormalities in DC without any further elaboration of the details (13,14). A previous study on familial idiopathic interstitial pneumonia (F-IIP) cases enrolled in a national research program reported that, despite fibrosis in all cases, the diagnostic features of UIP were seen in less than 50% (15).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Other DC manifestations are pulmonary and hepatic fibrosis, with portal hypertension, cerebellar hypoplasia and atresia of the lacrimal ducts 26 27. In the present case, other features can be explained by the disease, such as intrauterine growth restriction in pregnancy, thin hair and dental caries 12 18–21 23–25…”
Section: Discussionmentioning
confidence: 71%
“…The classic disease triad, present in about 90% of DC cases, includes nail dystrophy, mucosal leukoplakia and changes in skin pigmentation 10–14 17–22 24 25 27. These clinical features are not usually present at birth, but often appear in childhood, with a variable age at diagnosis (median 15 years, range 0–75 years) 10 13 18 25.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations